A Half-Hearted Defense of the Categorical Approach - Chad Flanders (Washington University Law Review, 2018)
One of Professor Magarian’s more impressive achievements in Managed Speech is paying the Roberts Court the compliment of providing a theory that runs through its various First Amendment cases. The book shows us surprising and hidden connections between disparate opinions by the Justices of the Court, and between different areas of First Amendment law. Importantly, the “managed speech” theory goes beyond just name-calling: “managed speech” is a coherent and even possibly defensible theory, not a label, like calling the Court “right-wing” or “pro-Business.” But there are some problems with Magarian’s approach. The first is that it works better for some areas of First Amendment law (government speech, campaign finance) than others—as Magarian himself might admit. A second problem is that Magarian’s alternative, “dynamic diversity,” is not as fully fleshed out as “managed speech,” so his book, in the end, operates more in the mode of diagnosis and critique rather than a positive blueprint for change. I will have something more to say about this in what follows. But it is a third problem I mostly want to focus on in my short essay in this Symposium. Dynamic diversity, like managed speech, operates at the level of theory, not at the level of constitutional doctrine. So while it may be clear what results in cases dynamic diversity would like, it is less clear what doctrinal route we should take to get to those results. In trying to figure out what route dynamic diversity could take, I make a partial—and somewhat half-hearted—defense of the Court’s so-called categorical approach, developed in Stevens, Brown, and Alvarez, and about which Magarian seems ambivalent. I think there is a lot to be said for the categorical approach, and even its reliance on the perhaps malleable and certainly vague idea of “tradition.” Maybe the categorical approach is not our first choice or the choice for understanding the First Amendment. But it might just work as a second-best compromise in a lot of ways, and it may be the best way doctrinally to realize some of the goals of “dynamic diversity.” My paper has three parts. In the first, I describe the appeal of the categorical approach, giving my own impressionistic view of where and why some people tend towards favoring First Amendment speech protections (including myself). In the second part, I try to list some of the problems with dynamic diversity. It is not only underdeveloped as a doctrinal matter—an objection I pursue more in the third part—but it is also strangely undermotivated as a theory. Stability has its appeal; less obvious is why disruption or social and political change as such are valuable. I also question whether dynamic diversity can support the results in Brown, Stevens, and Alvarez—which Magarian says he favors. In the third part, I turn more explicitly to doctrine and defend the categorical approach against some of Magarian’s brickbats.
Keywords: Managed Speech; Categorical approach; First amendment; Dynamic diversity; Roberts Court; Speech protections; Greg Magarian